The Influence of Work Discipline and Work Environment on Compliance with Patient Safety Procedures among Health Workers at the Beriman Balikpapan Regional Hospital - Rachmatullah, Fahmi; Purwadhi, Purwadhi; Suwardhani, Achmad Dheni (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Compliance with patient safety procedures is a crucial component in improving the quality of hospital services. This study aims to analyze the influence of work discipline and work environment on healthcare workers’ compliance with patient safety procedures at RSUD Beriman Balikpapan. The research used a quantitative method with a descriptive-verificative approach. Data were collected through questionnaires distributed to 207 healthcare worker respondents and analyzed using multiple linear regression with validity, reliability, normality, multicollinearity, and heteroscedasticity tests. The results showed that work discipline and work environment variables had a simultaneous and significant effect on compliance with patient safety procedures. Partially, work discipline had a significant influence with a greater contribution compared to the work environment. The coefficient of determination indicated that these two variables explained 52.2% of the compliance with patient safety procedures, while the remaining percentage was influenced by other variables not examined in this study, such as work culture, motivation, and workload. These findings suggest that improving discipline and enhancing the work environment can be effective strategies to encourage healthcare workers to comply with patient safety procedures. Other factors beyond this study, such as organizational culture or workload, are also suspected to influence the level of compliance.